We Don't Need No Education: The Effect of Natural Resource Income Shocks on Human Capital - Mark Gradstein; Phoebe W. Ishak (Institute of Labor Economics (IZA), 2020)
We explore the effects of persistent income shocks on human capital using oil price fluctuations in a large sample of relevant African countries and employing micro data from multiple waves of the Demographic and Health Survey (DHS). Theoretically, such shocks enable human capital investment via the standard income effect; but also crowd it out because of substitutability between natural resource and human capital income sources - so the net outcome can go either way. Our model also suggests that the relative strength of the two effects depends on the age at which the shock is experienced and the affected gender. Consistent with these insights, we find that income shocks in early life enhance educational attainment and other derived outcomes; but reduce them if experienced in adolescence, especially for females. These results survive multiple robustness checks, and their broader implications are discussed.
Keywords: O12; I2; 330; natural resources; income shocks; human capital